Sequential learning of communication skills in medical schools - Guillén-López, Otto (2019)
Communication skills in medicine are very important not only in the development of a physician’s clinical skills but in the doctor-patient relationship; and, besides, has beneficial results in the same patient. However, its learning is neither explicit nor structured in most of our medical schools. This article’s objective is to summarize a proposal in order that such skills be included in the curricular plans of our medical schools.